How to strengthen the cooperation between institutions of health education and clinical practice : The experience of testing shared positions - Wangen, Margret Gyda; Mary-Elizabeth Bradley Eilertsen; Askim, Torunn; Rødahl Thingnes , Elin; Solberg, Hilde Strøm; Granbo, Randi (Nordisk Tidsskrift for Helseforskning, 2021)
In a pilot project aimed at testing the idea of shared positions, five hospital employees and five university employees from four different health educations participated. Each of them held a 20% position devoted to the collaboration. The purpose of this study is to examine the expectations and experiences regarding positions established to promote cooperation. The collection of data took place through focus group interviews before and after the project, with those employed in the positions participating as informants. The analysis of data was inspired by Malterud’s systematic text condensation. The results reveal that leaders and staff from both the field of education and clinical practice ought to be involved in the development of shared positions. The shared positions may help boosting the status of clinical practice within the education by opening up new arenas of cooperation. The introduction of a systematic approach through new pedagogic tools like the SVIP model and primary supervisor model could strengthen the role of supervisors in clinical practice and provide them with more skills in the supervision of students. New pedagogic meeting points and a clearer distribution of responsibilities in the clinical supervision of students will also enable closer cooperation between the fields of education and clinical practice.
Keywords: Health professionals education; supervision in clinical practice; joint arenas of cooperation; culture for clinical practice supervision; shared positions; SVIP (strengthened clinical supervision)